2003
DOI: 10.1023/a:1022809430756
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The objective of this study was to characterize the prevalence of asymptomatic liver transminase (LT) abnormalities in a healthy, low-risk adult population and identify associated risk factors. We reviewed 2340 completed medical records of participants in our Executive Health Program, which provided screening medical evaluations for executives. LT (alanine aminotransferase and aspartate aminotransferase) were considered abnormal if they above normal range for our laboratory. Subjects were excluded if they had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Even after multivariate adjustments for factors previously found in other studies to be associated with differing ALT levels (sex [2], [4], [7], [8], [11]; alcohol use [7]; components of the metabolic syndrome [4][11]: BMI, waist-hip ratio, diabetes, fasting glucose, total cholesterol to HDL ratio, triglycerides), for surrogate markers of adiposity (leptin [4], IL-6 [27], [28], adiponectin [29], [30], ghrelin [31], [32]), and for other markers of liver function (bilirubin, GGT, albumin), the association of rising age with decreasing ALT remained significant (p<0.0001, Table 2). Correspondingly, the extreme values of ALT (95 th percentile cutoff points for upper limit of ALT, Figures 1 and 2) as well as the prevalence of elevated ALT (p<0.0001, Figure 3) both decreased with rising age as well.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Even after multivariate adjustments for factors previously found in other studies to be associated with differing ALT levels (sex [2], [4], [7], [8], [11]; alcohol use [7]; components of the metabolic syndrome [4][11]: BMI, waist-hip ratio, diabetes, fasting glucose, total cholesterol to HDL ratio, triglycerides), for surrogate markers of adiposity (leptin [4], IL-6 [27], [28], adiponectin [29], [30], ghrelin [31], [32]), and for other markers of liver function (bilirubin, GGT, albumin), the association of rising age with decreasing ALT remained significant (p<0.0001, Table 2). Correspondingly, the extreme values of ALT (95 th percentile cutoff points for upper limit of ALT, Figures 1 and 2) as well as the prevalence of elevated ALT (p<0.0001, Figure 3) both decreased with rising age as well.…”
Section: Discussionmentioning
confidence: 88%
“…A study of serum ALT concentrations in healthy Iranian blood donors also concluded that ALT did not correlate with age [15]. However, a few studies published since that time have reported that the prevalence of elevated (abnormal) ALT decreases with age [4], [6], [7], [8], [10], [11]. Some have found this association to be true in men, but not in women [3], [5], [16].…”
Section: Introductionmentioning
confidence: 98%
“…Our gold standard definition for verifying NAFLD derived from chart review was elevated liver enzymes ( i.e ., ALT >40IU/ml for males and ALT>31IU/ml for females 7,8 ) and no other documented liver diseases (HCV, HBV, alcoholic liver disease, and other less common etiologies of chronic liver disease) in the presence of either: (1) a histological diagnosis of NAFLD, (2) radiological NAFLD features such as fatty liver, increased or heterogeneous echogenicity, or (3) patients not meeting criteria #1 or #2 but had features of metabolic syndrome defined as two or more of the following: BMI > 25, hypertension defined by systolic blood pressure ≥130 mmHg or diastolic blood pressure ≥ 85 mmHg; high density lipoprotein (HDL) < 40g/dl; triglycerides >150mg/dl; or presence of diabetes (hemoglobin A1c (HbA1c) >7.0). For each measurement, if there were multiple values we used the value that was closest to the date of the first elevated ALT.…”
Section: Methodsmentioning
confidence: 90%
“…A study in healthy Iranian blood donors found no correlation between ALT and age (15), but others have reported that the prevalence of elevated ALT decreases with increasing age. (4,68,10,11,16) Most of these studies were performed using retrospective chart reviews of patients who had laboratory tests for medical reasons, in self-selected populations (such as blood donors), or in Asian populations, whose liver function may differ compared to Western populations.…”
Section: Introductionmentioning
confidence: 99%